Efecto de la temperatura y la acidificación en larvas de Strombus gigas (Mesogastropoda: Strombidae) - Chavez Villegas, Jose Francisco (2017)
The increase in CO2 emissions produces heating and reduced pH in the oceans, which may have negative effects on many marine organisms. This is particularly important for those with calcified structures such as the molluscs and their larval stages. We studied Strombus gigas larvae, a gastropod of commercial importance in the Caribbean Sea, in order to know the effect of water temperature and acidification on their development, growth, mortality and calcification during the larval period. A larval culture with triplicate samples was carried out employing four treatments of temperature and pH (Control = 28 °C - pH 8.1, T1 = 28 °C - pH 7.6, T2 = 31 °C - pH 8.1 and T3 = 31 °C - pH 7.6) in August 2015. We registered hatching (No. of eggs – No. of larvae hatched) and organs development, while shell growth and mortality ratio were evaluated over time. Shell calcification was studied in 30 days old larvae using EDX and RAMAN analysis. Our results showed that organs development and shell growth were higher at 31 °C treatments (initial size of 230 ± 4.12 to 313.27 ± 11.34 µm, and final size from 829.50 ± 11.33 to 1 054.50 ± 11.13 µm; from T1 to T2 respectively), and the same pattern was recorded for hatching time (18 hr) and mortality rate (~ 57 %). The Calcium proportion (% wt) was similar between treatments (34.37 ± 10.05 to 37.29 ± 16.81 % wt). Shell Raman analysis showed aragonite in all experimental treatments, with the highest values in the control (1 039.54 ± 780.26 a.u.). Calcite was detected only in 31 °C treatments (174.56 ± 127.19 a.u.), while less intensity of aragonite and calcite were registered at pH 7.6. In conclusion, S. gigas could be adapted to ocean future predictions, however, shell biomineralization processes can be affected.